2006
DOI: 10.4049/jimmunol.176.12.7715
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T Cells Play Major Effector Role and CD8 T Cells Initiating Role in Spontaneous Autoimmune Myocarditis of HLA-DQ8 Transgenic IAb Knockout Nonobese Diabetic Mice

Abstract: In humans, spontaneous autoimmune attack against cardiomyocytes often leads to idiopathic dilated cardiomyopathy (IDCM) and life-threatening heart failure. HLA-DQ8 transgenic IAb knockout NOD mice (NOD.DQ8/Ab0; DQA1*0301, DQB1*0302) develop spontaneous anticardiomyocyte autoimmunity with pathology very similar to human IDCM, but why the heart is targeted is unknown. In the present study, we first investigated whether NOD/Ab0 mice transgenic for a different DQ allele, DQ6, (DQA1*0102, DQB1*0602) would also deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Transgenic over-expression of MCP-1 by myocardial tissue indicates that recruitment of Mø is sufficient to induce myocarditis (36). However, there are substantial numbers of T cells in the heart and lung of PD-L1−/−; MRL mice and there is a central role for T cells in other spontaneous models of myocarditis (37-39). While CD8 + T cells initiate disease, CD4 + T are the primary effectors (39).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic over-expression of MCP-1 by myocardial tissue indicates that recruitment of Mø is sufficient to induce myocarditis (36). However, there are substantial numbers of T cells in the heart and lung of PD-L1−/−; MRL mice and there is a central role for T cells in other spontaneous models of myocarditis (37-39). While CD8 + T cells initiate disease, CD4 + T are the primary effectors (39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CD4 + T cells are the major effector cells in myocarditis in DQ8 + NOD mice (24,39). However, the antigen specificity of the pathogenic CD4 + T cells was not defined, and the T cell assays were performed with cardiac myosin isolated from porcine heart (7,39), which predominantly expresses β-MyHC (40), so that the contribution of reactivity to α-MyHC was difficult to assess.…”
Section: Figurementioning
confidence: 99%
“…Although CD8 1 T cells are primarily considered to play a role as effectors of target cell killing, they may also be important in disease establishment [6,7]. CD4 1 T cells, on the other hand, contribute to autoimmune and inflammatory diseases in a wide variety of ways.…”
mentioning
confidence: 99%